An adaptive refined grid search strategy for assessing operational flexibility and application on refrigerant selection. Issue 4 (20th January 2022) - Wang, Jiayuan; Smith, Robin; Zhu, Lingyu
Abstract: A novel adaptive refined grid search strategy is developed for representative characterization of process feasible region boundaries and accurate estimation of its hypervolume. In particular, a linked list data structure adopted from the field of computer science is used to maintain the grid connectivity information. A uniform perturbation scheme is used to refine the search only near the boundaries. The volumetric flexibility index ( FI V ) is calculated directly from a summation of feasible hypercubes in the grid, without the need to apply shape reconstruction techniques. The proposed adaptive grid search strategy can capture complex region shapes with reduced sampling costs and without randomness, increasing reproducibility. Operational flexibility is optimized traditionally at a process scale. A case study on refrigerant selection is presented to demonstrate that the developed strategy can be combined within a computer‐aided molecular design framework for operational flexibility optimization at the molecular scale.